Euro Adoption in Central and Eastern Europe : Opportunities and Challenges - Schadler, Susan (International Monetary Fund, 2005)
Eight central and eastern European countries--the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovak Republic, and Slovenia--officially joined the European Union (EU) in May 2004. This auspicious milestone marked the beginning of the next major step for these countries in their move toward full integration with the EU-adoption of the euro. Seeking to consider the opportunities and challenges of euro adoption, the papers in this volume--by a noted group of country officials, academics, representatives of international institutions, and market participants-offer insight on the various dimensions of euro adoption in these eight new EU members--how they should prepare, whether an early move is optimal, and what pitfalls may occur along the way.